AB0511 Vitamin d: potential role in antiphospholipid syndrome. (15th June 2017) - Riancho-Zarrabeitia, L; Cubería, M; García-Canale, S; Daroca, G; García-Unzueta, M; Hernández, JL; Lόpez-Hoyos, M; Muñoz, P; Agudo, M; Martínez-Taboada, V
Abstract : Background: Vitamin D, due to its immunoregulatory properties, has been implicated in the pathogenesis of autoimmune diseases, such as antiphospholipid syndrome (APS). Objectives: A) To determine vitamin D levels in patients with primary APS and to compare them with patients with positive antiphospholipid antibodies (aPL), not meeting clinical criteria for APS, and with healthy controls. B) To analyze the association of the vitamin D levels with both the clinical manifestations and the immunological profile of patients with primary APS. Methods: We conducted a retrospective study including patients attended at the rheumatology clinic from a tertiary facility in Northern Spain. We included 74 patients with primary APS, 54 patients with positive aPL serology not meeting clinical criteria for APS and 326 healthy controls adjusted by the month of vitamin D analysis. We considered 30 ng/ml and 10 ng/ml as the thresholds for vitamin D insufficiency and deficiency, respectively. Results: Median levels of vitamin D were similar in the three groups: 21 (range 5–69) in primary APS, 25 (4–50) in the aPL-positive group, and 21 (4–105) in controls. Overall, 53.9% of measurements were performed during the sunny season (April to September). Ten percent of patients with primary APS were males, versus 16% in the aPL serology group and 26% among healthy controls (p=0.007). Mean age was 46±15 in primary APS, 49±17 in the aPL-positive group and 53±10 in the control group (p<0.001). Regarding vitamin D insufficiency, 82% of APS patients had levels of vitamin D (<30 ng/ml) versus 70% and 72% of patients with aPL serology and controls, respectively (p=0.168). When analyzing the prevalence of vitamin D deficiency (<10 ng/ml), we found significant differences across the groups: 16.2% in patients with primary APS, 11.1% in patients with positive serology and only 4.9% in healthy controls (p=0.002). There was no significant association between insufficient levels of vitamin D and the presence of thrombotic or obstetric events. Nevertheless, we found a trend for the presence of more thrombotic events in patients with vitamin D deficiency (p=0.097). Regarding the immunological profile, we found no association between vitamin D and either the number of positive antibodies or their serological evolution. However, we found an association between insufficient levels of vitamin D and the presence of lupus anticoagulant (54.7% vs 18.2%, p=0.047) Conclusions: More than 80% of patients with primary APS have insufficient levels of vitamin D and 16% of them have very low levels of vitamin D. Primary APS patients show a higher frequency of vitamin D deficiency than healthy controls. Patients with vitamin D insufficiency have more commonly positivity for lupus anticoagulant. Disclosure of Interest: None declared